2018
DOI: 10.5650/jos.ess17281
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Solvent Type and Roasting Processes on Physico-Chemical Properties of Tigernut (<i>Cyperus esculentus L.</i>) Tuber Oil

Abstract: In this study, physico-chemical properties of raw and roasted tigernut oils extracted by two different solvents were determined. Peroxide values of raw and roasted tigernut oils extracted by petroleum ether and n-hexane solvents changed between 0.83 and 0.91 meqO/100g to 1.57 and 1.63 meqO/100g, respectively. While oleic acid contents of raw tigernut oils extracted by petroleum ether and n-hexane are determined as 66.83 and 67.47%, oleic acid contents of roasted tigernut oils extracted by petroleum ether and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…it can be observed that TNTF oil was rich in unsaturated fatty acids (79.94%), These results agree with These results were in agreement with those reported by (Aljuhaimi et al, 2018) andSabah, et al (2009). Tiger nut oil is rich in phytosterols, tocopherols and essential unsaturated fatty acids (Mohdaly, 2019).…”
Section: ‫النوعية‬ ‫التربية‬ ‫مجاالت‬ ‫في‬ ‫البحوث‬ ‫مجلة‬supporting
confidence: 93%
“…it can be observed that TNTF oil was rich in unsaturated fatty acids (79.94%), These results agree with These results were in agreement with those reported by (Aljuhaimi et al, 2018) andSabah, et al (2009). Tiger nut oil is rich in phytosterols, tocopherols and essential unsaturated fatty acids (Mohdaly, 2019).…”
Section: ‫النوعية‬ ‫التربية‬ ‫مجاالت‬ ‫في‬ ‫البحوث‬ ‫مجلة‬supporting
confidence: 93%
“…Tigernut tubers are rich in lipids, proteins, starches, dietary fibers, and vitamins, which are usually applied to develop edible oil, plant milk, and snack food (Clemente‐Villalba et al, 2021; Oluwajuyitan & Ijarotimi, 2019). The extraction and physicochemical characterization of tigernut tuber oil have been widely reported (Aljuhaimi, Ghafoor, et al, 2018; Aljuhaimi, Simsek, & Ozcan, 2018). But there are few types of research on tigernut tuber starch (TTS).…”
Section: Introductionmentioning
confidence: 99%
“…Lipid peroxidation in oils is measured by the determination of peroxides which form as the primary reaction products during oil oxidation. Peroxide value is, therefore, used as an indication of oxidative rancidity in unsaturated fats and oils [19]. As determined by this research, the peroxide value of T. pedataseed kernel oil is 0.9641±0.2021 meq O 2 /Kg.…”
Section: Discussionmentioning
confidence: 69%